A conceptualization of vehicle platoons and platoon operations. (July 2017) - Maiti, Santa; Winter, Stephan; Kulik, Lars
Highlights: A conceptualization of a platooning objects and platoon properties. The identification and abstraction of platoon operations. A demonstration – how platoon objects, properties, and operations interact to enable any complex behavior. Abstract: Vehicle platooning, a coordinated movement strategy, has been proposed to address a range of current transport challenges such as traffic congestion, road safety, energy consumption and pollution. But in order to form platoons in an ad-hoc manner the vehicles have to 'speak the same language', which is in current practice limited to vehicles of particular manufacturers. There is no standard language yet. Also in research, while the current literature focuses on platoon control strategies, intra-platoon communication, or platooning impacts on traffic, the conceptualization of platooning objects and their operations remained unattended. This paper aims to fill this fundamental gap by developing a formal model of platooning concepts. The paper proposes an ontological model of platooning objects and properties and abstract basic building blocks of platoon operations that can then be aggregated to complex platooning behavior. The presented ontological model provides the logical reasoning to support vital decision-making during platoon lifecycles. The ontological model is implemented and demonstrated.